A Multi-County Health District's Journey to Accreditation: The Challenges and Benefits - Tara Echols (Georgia Southern University, 2017)
Background: In September 2011, the Gwinnett, Newton, and Rockdale Health Departments began to discuss accreditation. We regarded accreditation as a way to highlight our strengths and identify areas for quality and performance improvement as well as an opportunity to improve our capacity for greater accountability, increased efficiency and improved process flow. We further viewed it as a means to successfully carry out our mission, and effectively deliver the core functions and ten essential public health services. Methods: With financial backing from Healthcare Georgia Foundation and technical assistance from Georgia Southern University, the Gwinnett, Newton and Rockdale County Health Departments began its pursuit of accreditation by assessing department processes, policies, and procedures for alignment to the Public Health Accreditation Board (PHAB) standards. This resulted in identified areas for improvement and needed policy and procedure development. The Model for Improvement was actively used throughout our pursuit of accreditation, and we viewed the process as several inter- related plan, do, check, act (PDCA) cycles. After being advised on several options, we changed our application from multi-jurisdictional to a local health district based on guidance from PHAB for all the health districts in Georgia. Domain leads were assigned; these later developed into domain teams comprised of individuals with expertise in various relevant areas. The teams met on a regular basis to review domain documentation and to discuss the 'story' it tells about our department. We prepared for the site visit by conducting a mock site visit using local PHAB site visitors. This experience was extremely helpful in calming the participant staff and identifying areas that we could improve. Results: After several iterations of guidance from PHAB on how we should apply we applied as a local public health district. With feedback from our mock site visit we were able to prepare for and successfully complete our site visit with no request to reopen any measures. We received a stellar site visit report with 93% of the measures scored 'fully demonstrated' and 7% scored 'largely demonstrated'. Our department was accredited on August 17, 2016 as the 3rd accredited health district in the State of Georgia. Conclusions: The process of pursuing accreditation has been a challenge on various fronts; from indecision about how we should apply, to uncertainty about interpretation of the standards, to hesitance about choosing county-specific or departmental documentation. However, the culture of quality and solidified community partnerships that resulted from this process are invaluable. Key words: accreditation, quality improvement, accountability, efficiency